Beneficios de la urea oral en pacientes con hiponatremia e insuficiencia cardiaca - ANGEL MARTINEZ GONZALEZ; AVELINO RODRIGUEZ GONZALEZ; MONICA CORRAL ZAS; EMMANUEL REYES MOREL; ALEJANDRO ISMAEL LORENZO POUSO; JOSE MANUEL GOMEZ SOUSA; SAMUEL RODRIGUEZ ZORRILLA (Sociedade Galega de Medicina Interna, 2022)
OBJECTIVES: To assess the efficacy and safety of oral urea in patients with hyponatremia and heart failure (HF). METHODS AND RESULTS: This is a retrospective observational study of hospitalized and non-hospitalized patients with HF and hyponatremia (serum Na+ < 135 mEq/L) followed by the Heart Failure Unit between January 2013 and May 2018. The study evaluated sodium normalization levels (Na+ = 135 ± 3 mEq/L) after treatment with oral urea. Thirty-four patients were included in the study, and all were on standard treatment for HF. Natremia at the beginning of treatment with oral urea was 126.34 ± 5.41 mEq/L, and the mean on the day of normalization was 136.45 ± 3.22 mEq/L (p < 0.001). The mean time to achieve sodium normalization was 4.28 ± 2.37 days. Blood urea at the beginning of treatment with urea was 85.77 ± 50.51 mg/dl, and the mean on the day of Na+ normalization was 137.90 ± 56.66 mg/dl (p < 0.001). There was an increase in diuresis (p < 0.006) and plasma osmolarity (p < 0.001) as well as a slight decrease in serum potassium (p < 0.001). The mean dose of oral urea was 22.5 g/day. There were no important adverse effects, nor were there significant changes in creatinine levels or the estimated glomerular filtration rate by the MDRD formula. CONCLUSIONS: When added to the standard treatment for short periods of time, treatment with oral urea is safe and effective at correcting natremia and improving diuresis in patients with hypervolemic HF with hyponatremia.